Transition in care interventions for Refugee, Immigrant and other Migrant (RIM) populations: a health equity-oriented scoping review - Liu, Amy; Yazdani, Yasaman; Elias, Manahel; Patel, Krisha; Budzi, Divine; Saad, Ammar; Pottie, Kevin (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Transition in care involves the transfer of responsibility for aspects of patient and public health care among providers, institutions, and health and social sectors. Indeed, health systems increasingly require individuals to interact with a number of providers, in a number of health settings, and across multiple points of time. Refugees, immigrants, and migrant (RIM) individuals face several precarious transitions, language and cultural barriers, and unfamiliarity with public health systems, which may result in health inequities. A greater understanding of the interventions that facilitate effective transitions in care for RIM populations is needed to improve health outcomes in this vulnerable group. Methods This health equity-oriented scoping review aimed to report the characteristics of Transition in Care (TiC) interventions for RIM populations and identify which equity-relevant characteristics of RIM populations were targeted by these interventions. We searched MEDLINE, Embase, and Scopus for eligible studies published in English from the year 2000 onward. Two independent reviewers screened search records and extracted relevant data from included studies. We used a public health and health equity lens to identify the social determinants of health that were addressed by TiC interventions. Results Our systematic search identified a total of 42 studies, evaluating the impact of 38 unique interventions or public health programs. The delivery of interventions involved various healthcare sectors and professionals. Additionally, some programs enlisted non-medical personnel to provide health-related education and support. The most promising programs for health outcomes involved health navigation or providing public health education for RIM populations. The most common equity-relevant characteristics considered in these studies were language, cultural background, and education level. Conclusion This novel scoping review reveals a diverse range of public health interventions that are being implemented to improve national and international transitions in care for RIM populations, with the most promising from healthcare navigation and health education. Future research should target transitions to digital health technologies, public health, hospital-to-home, and pediatric to adult care gaps to ensure smoother transitions in care for equity-deserving populations navigating new healthcare systems.